2009
DOI: 10.1111/j.1365-2966.2008.14372.x
|View full text |Cite
|
Sign up to set email alerts
|

Spot activity in the RS CVn binary DM Ursae Majoris

Abstract: We present extensive UBVRI photometry of the active RS CVn binary DM UMa obtained at two different observatories over 1988–2008. We find the light curve of the star to be highly variable. The long‐term photometry shows no evidence of any cyclic spot activity. On one occasion, the amplitude of modulation in V band was 0.30 mag, a rather high value for an active star in a binary seen at a comparatively low orbital inclination. The mean V magnitude of DM UMa during 1993–94 was brighter than that over 1979–85 by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Because of the small temperature variation during the years with available V − I C , we cannot estimate the contribution of the changes of temperature origin in the overall light variation. However, the B − V color index, which also reflects the temperature variability as seen from the rotationally modulated light and color index curves in Rosario et al (2009), does not show the long-term change evident in V color. This is at least suggestive that some other mechanism is responsible for that variation (see Fig.…”
Section: Temperatures and Luminosities From Long-term Photometrymentioning
confidence: 91%
See 3 more Smart Citations
“…Because of the small temperature variation during the years with available V − I C , we cannot estimate the contribution of the changes of temperature origin in the overall light variation. However, the B − V color index, which also reflects the temperature variability as seen from the rotationally modulated light and color index curves in Rosario et al (2009), does not show the long-term change evident in V color. This is at least suggestive that some other mechanism is responsible for that variation (see Fig.…”
Section: Temperatures and Luminosities From Long-term Photometrymentioning
confidence: 91%
“…5. DM UMa showed nearly constant mean B − V during the 28 years of observation (but still rotationally modulated) while its V magnitude changed more than 0. m 6 in total (Rosario et al 2009). The low inclination of about 40…”
Section: Cyclic Brightness and Color Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…4 are not consistent with the general understanding that the light modulations in RS CVn binaries are caused by starspots that are cooler than the ambient photosphere, in which case we would have observed a redder colour for V711 Tau at fainter visual magnitudes. From an analysis of an extensive multicolour photometry of the single-lined, active RS CVn binary DM UMa, Rosario et al (2009) found that there are excess fluxes in U and B bands, which increase as the star becomes fainter, but they compensate only partially for the greater reduction in flux in those bands caused by spot activity.…”
Section: (B -V) Colour Variationmentioning
confidence: 99%